Intensive lipid‐lowering therapy in the 12 months after an acute coronary syndrome in Australia: an observational analysis. Issue 2 (22nd November 2018) - Brieger, David; D'Souza, Mario; Hyun, Karice; Weaver, James C; Kritharides, Leonard
Abstract: Objective: To determine the prevalence and identify predictors of people hospitalised with acute coronary syndrome (ACS) receiving intensive lipid‐lowering therapy during the 12 months after their discharge from hospital. Design: Retrospective observational analysis. Setting: Data were extracted from CONCORDANCE, a prospective, Australian investigator‐initiated ACS registry. Participants: Patients enrolled in CONCORDANCE during January 2015 – May 2016 who survived to hospital discharge, for whom information on lipid‐lowering therapy 6 or 12 months after discharge from hospital were available. Main outcome measures: Not receiving intensive lipid‐lowering therapy (with or without ezetimibe) at the most recent follow‐up (6 or 12 months); predictors of not receiving intensive lipid‐lowering therapy. Results: 1876 of 3441 patients (55%) were receiving intensive lipid‐lowering therapy 6 or 12 months after their hospitalisation with an ACS. Predictors of not receiving intensive lipid‐lowering therapy included not been prescribed this treatment prior to their hospital admission (odds ratio [OR], 1.53; 95% CI, 1.26–1.85) or at hospital discharge (aOR, 7.24; 95% CI, 4.37–12.0), being a woman (aOR, 1.20; 95% CI, 1.02–1.41), and not being referred for cardiac rehabilitation (aOR 1.39; 95% CI, 1.09–1.78). Patients who were managed medically in hospital (not revascularised; aOR, 1.54; 95% CI, 1.25–1.91) or underwent coronary artery bypass grafting (aOR 1.55; 95% CI, 1.26–1.92) were less likely to be receiving intensive lipid‐lowering therapy at follow‐up than those with a percutaneous coronary intervention. Unmeasured hospital factors accounted for 17% of the variation in the likelihood of intensive lipid‐lowering therapy. Conclusions: 45% of patients in Australia are not receiving intensive lipid‐lowering therapy in the 12 months after their ACS. Optimising oral lipid‐lowering therapy would reduce the recurrence of coronary events in this high risk group.